Eleven kids, one summer - Martin, Ann M. 1955- (New York Scholastic, 1991)
Adventures of a family with eleven children as they summer on the beach at Fire Island.
Keywords: Family life -- Fiction; Vacations -- Fiction; Fire Island (N.Y.) -- Fiction